2021
DOI: 10.1038/s41419-021-03531-z
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting β-catenin disables nucleolar functions in triple-negative breast cancer

Abstract: Triple-negative breast cancer (TNBC) patients with upregulated Wnt/β-catenin signaling often have poor clinical prognoses. During pathological examinations of breast cancer sections stained for β-catenin, we made the serendipitous observation that relative to non-TNBC, specimens from TNBC patients have a greater abundance of nucleoli. There was a remarkable direct relationship between nuclear β-catenin and greater numbers of nucleoli in TNBC tissues. These surprising observations spurred our investigations to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…For instance, Dr. Vincent’s studies show that the induction of ribosome biogenesis is a general feature of the EMT program and can promote the cellular plasticity and migration ( 42 ). Similarly, except for contributing to the ribosomal biogenesis, LAS1L has also been reported to be involved in tumor cell proliferation ( 18 ), metastasis ( 20 ) and autophagy ( 19 ). Among them, Dr. Samant ‘s research shows that knockdown of LAS1L leads to a sharp reduction in tumorigenic and metastatic properties in triple-negative breast cancer ( 20 ), which is similar to Dr. Vincent’s conclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Dr. Vincent’s studies show that the induction of ribosome biogenesis is a general feature of the EMT program and can promote the cellular plasticity and migration ( 42 ). Similarly, except for contributing to the ribosomal biogenesis, LAS1L has also been reported to be involved in tumor cell proliferation ( 18 ), metastasis ( 20 ) and autophagy ( 19 ). Among them, Dr. Samant ‘s research shows that knockdown of LAS1L leads to a sharp reduction in tumorigenic and metastatic properties in triple-negative breast cancer ( 20 ), which is similar to Dr. Vincent’s conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…The crucial role of LAS1L in tumor progression is being revealed. A recent study from Dr. Samant also showed that knockdown of LAS1L leads to a reduction in proliferation and metastatic potential of triple negative breast cancer cells (20). However, studies on the AS regulation of LAS1L in tumor have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Dyskerin is an essential nucleolar protein that can affect the growth of tumors through its related mechanism of rRNA processing in the precursor (33); the rRNA synthesis inhibitor CX-5461 can induce acute lymphocytes by activating the ATM/ATR pathway, leukemia cells stagnate and die (34). The growth of triple-negative breast cancer requires high-demand ribosome biosynthesis (35); ribosome biogenesis can affect the biological behavior of cell senescence and cancer through a connection with the target of the rapamycin (TOR) signaling pathway (36). The above evidence indicates that RRP12 can also affect the occurrence and development of tumors by affecting the synthesis and metabolism of ribosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Sustained elevated ribosome biogenesis is one of the classical hallmarks of aberrant cell growth. With its distinct pathological features in malignant cells, the nucleolus has attracted recent attention as a novel drug target [ 31 , 69 , 70 ]. Many structurally diverse molecules have been reported to directly or indirectly perturb the dynamic functionality of the nucleolus [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that triple-negative breast cancer (TNBC) cells are more reliant on elevated rRNA biogenesis [ 31 ]. Thus, in this study, we use two human TNBCs, SUM159 and MDA-MB-468, and one metastatic murine mammary cancer cell line 4T1.…”
Section: Methodsmentioning
confidence: 99%